Attitudes and behaviors of African-American and Mexican-American women delivering newborns in inner-city Los Angeles. - Gray, S. (National Medical Association, 1995)
To study some of the factors relating to the care of mothers and newborns in an inner-city hospital, three sources of information were reviewed: an obstetric database including information on prenatal care and perinatal mortality, a database of all admissions to the hospital neonatal intensive care unit over the past 5 years, and a detailed questionnaire concerning attitudes and behaviors of recently delivered women. While analyses from these hospital-based data are not conclusive, the results add evidence for the following propositions: 1) Optimal prenatal care is infrequently obtained by mothers delivering at inner-city hospitals. Lack of prenatal care is clearly associated with increased perinatal mortality. While the need for prenatal care is appreciated by 98% of the mothers in this sample, the most frequent reasons why prenatal care is not obtained earlier or more frequently involve knowledge about and access to prenatal care. 2) Inner-city mothers, in general, manifest attitudes and behaviors that promote the welfare of their pregnancies and newborns. These attitudes and behaviors are in stark contrast to those that are frequently attributed to inner-city women by the media. 3) Acute perinatal medical and nursing care are perceived by many postpartum women as suboptimal, particularly in terms of the lack of respect shown to patients by nurses and doctors. 4) Improved acute obstetric and neonatal care improves perinatal morbidity and mortality of infants delivered at inner-city hospitals.